A QUALITATIVE RESEARCH ON THE PERCEPTION OF OCCUPATIONAL HEALTH AND SAFETY IN STORES OF TRADESPEOPLE OPERATING IN FOOD PRODUCTION - CEREV, Gökçe (Atlas Journal, 2020)
With the Occupational Health and Safety Law No. 6331 adopted in 2012, a new period began in Turkey in the field of Occupational Health and Safety. The law No. 6331 has a different structure than the previous legislation. With the law No. 6331, Occupational Health and Safety practices have reached a level encompassing all sectors without distinction between public and private sectors, and the enforcing approach of the previous legislation has turned into a preventive and guiding model. With the Law No. 6331, responsibilities were given to the employees, employers and the government and the ways of implementation were clarified. As a result of the expansion of the coverage area with the amendment made to the Law No. 6331, stores subject to the Law No. 5362 have entered into the application area of occupational health and safety legislation. Today, tradespeople are also obliged to fulfill the responsibilities of employers under the Law No. 6331. Tradespeople are not only important actors of regional trade but also contribute to the development of regional and national employment. This importance of tradespeople in terms of commerciality and employment is intended to be transformed into a healthier and safer structure with occupational safety practices. The approach and compliance of tradespeople to this transformation is important. In this study, occupational health and safety perceptions of tradespeople operating in food production sector were measured. Within the scope of the research, the owners of the businesses operating in Elazığ province, subject to Law No. 5362 and in food production were interviewed. In the study, interview technique, one of qualitative research methods, was used to measure the occupational health and safety perception of tradespeople in food production, and content analysis was applied to the results obtained. As a result of the analysis of the research data, it has been determined that the tradespeople do not have full knowledge about the changes in the occupational health and safety legislation, see the occupational safety practices as a cost element and that the chambers of tradespeople should be guiding them about occupational safety. Given the importance of tradespeople in the regional economy today, improving their knowledge of occupational health and safety has become a necessity.